The influence of performance-based management on teaching and research performance of Finnish senior academics. Issue 3 (3rd July 2017) - Kivistö, Jussi; Pekkola, Elias; Lyytinen, Anu
Abstract : Despite the widespread use of performance-based management in higher education, empirical research on its actual impact has remained scarce, particularly in Europe. With agency theory as a framework, our study utilised survey data collected from Finnish universities in order to explore the influence of performance management on perceived teaching and research performance of senior academics. Our findings suggest that, although academics hold a quite positive view of performance measurement as such, this attitude does not correlate with perceived high performance in either teaching or research. Moreover, our results suggest that perceived high performance among academics still relates primarily to acknowledgement from the academic community and academic achievement rather than to measurement and financial incentives.